Democratic Armament?: US-Democracy and Military Innovation during Periods of Transition - Wolf, Raimund (2013)
This disseration provides an answer to the question what influence societal preferences have on US military innovation. For this purpose, it connects theoretical threads from Governmental Political and New Liberalism with the literature on military innovation and democratic peace. Four periods of military transition during which the incentive for military innovation is particularly strong are analysed based on a structured-focused comparison: The Post-World War II (1945-1949), the Korean War period (1959-1953), the Post-Cold War (1990-1998) and the War on Terror period (2001-2007). The findings of this study show that the domestic and international levels of US military policy increasingly follow conflicting logics which reduce the likelihood of innovation. The public majority's interest in innovation as a means to maintain efficient military forces in a changing world remains latent most of the time. In contrast, special interest groups' preferences for the benefitial domestic status quo result in a permanent push towards military stability. Only in cases of perceived failure, the public majority actively engages in military policy and triggers reform through elections.
Keywords: Hochschulschrift; Demokratie; Militär; Waffe; USA